Biochelator Assisted Phytoremediation for Cadmium (Cd) Pollution in Paddy Field - Yangyang Wang (MDPI AG, 2021)
To evaluate the efficacy of biochelators for phytoremediation of cadmium (Cd), effects of biochelators (humic acid, HA; polyaspartic acid, PASP; rhamnolipid, RLs) and synthetic chelator (sodium tripolyphosphate, STPP) on the growth, accumulation, and antioxidant index of Cd were investigated in Iris sibirica L. The results indicated that the addition of HA increased the dry weight of leaves and stems, and the addition of PASP, RLs, and STPP increased the growth of leaves but inhibited the growth of stems. The determination of Cd accumulation indicated that HA decreased the content of Cd in all tissues, while the addition of PASP, RLs, and STPP increased the accumulation of Cd in stems and roots. In addition, the determination of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) activities indicated that the treatment of PASP and RLs increased the activities of antioxidant enzymes, which might be beneficial to the resistance of Cd for Iris sibirica L. Overall, these results indicated that biochelators may improve the phytoremediation efficacy of Iris sibirica L. on Cd polluted paddy field. Among the tested chelators, PASP exhibited the best comprehensive efficacy and the highest commercial potential.